Сurrent issues of compensation for property damage caused by road traffic accidents - Shaykhmetova, Zh.В.; Mukhanova, A.T.; Yerdeshova, Zh.I. (Bulletin of the Karaganda University “Law Series”, 2023)
The article aims to study the issues of legal liability for transport offenses regulated by the legislation of the Republic of Kazakhstan, examining the concept of the composition of transport offenses, issues of administrative and criminal liability, comparative analysis in the context of regions of the country for road traffic offenses. According to the indicators of the authorized bodies of the Republic of Kazakhstan, the reasons for traffic accidents are as follows: exceeding the speed limit, driving a vehicle while intoxicated, over- taking and driving into the oncoming lane, not keeping a distance, not observing traffic rules, breaking the rules for transportation of passengers, violation of the rules for pedestrian traffic, etc. The analysis of the degree of criminal and administrative liability associated with the increase of vehicles and the impact of economic growth was conducted. The improvement of transport relations is considered as a tool for the development of economic mechanisms. The article describes the issues of compensation for harm as a consequence of the development of road transport relations, and the need for a clear regulation of these relations by the rules of law. An important aspect is the issue of consolidating the legal status of subjects of road transport relations in regulatory legal acts. It must be remembered that although the development of road transport relations is beneficial for the country's economy, failure to comply with basic traffic rules carries the greatest danger.